Method for improving physical properties of Bi-phase-rich Mn2Sb-based alloy material
By introducing a diffusion source of rare earth elements and controlling its diffusion, the problem of affecting magnetic properties of Bi-rich grain boundary phase agglomeration in Mn2Sb-based alloy is solved, and the effect of improving the magnetic properties and multifunctional properties of the alloy is achieved.
Patent Information
- Application Number
- CN202411826795.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The Mn2Sb-based alloy has Bi-rich grain boundary agglomeration during the process of doping Bi elements, which seriously affects its magnetic properties.
By introducing the diffusion source Dy100-yCuy or Pr100-zGaz, the mass percentage is controlled between 2.9% and 30%, mixed with the parent phase alloy (Mn2Sb) 1-xBix, sintering and heat treatment are carried out to promote the diffusion of rare earth elements to the grain boundary and form a magnetic grain boundary phase.
It effectively improves the magnetic properties of Bi-phase-rich Mn2Sb-based alloy materials, reduces the phase change thermal hysteresis, and enhances the versatile properties of the alloy, such as giant magnetothermal effect, giant magneto-resistance effect, etc., expands its application prospects.
Smart Images

Figure CN119571118A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic phase change materials, and in particular relates to a method for improving the physical properties of a Bi-rich Mn2Sb-based alloy material. Background Art
[0002] Mn atoms have good magnetic moments and the advantage of low cost. Among these Mn-based intermetallic compounds, magnetic phase change materials Mn2Sb-based alloys stand out. This new type of magnetic functional material exhibits many rich and valuable physical properties and effects, such as kinetic trapping, spin reorientation, giant magnetocaloric effect, giant magnetoresistance effect, exchange bias effect and Hall effect, etc. It has important applications in some basic research fields of phase change physics as well as cutting-edge fields such as smart materials, information storage, and magnetic refrigeration.
[0003] While Mn2Sb-based alloys have rich physical properties and effects, their physical properties are not excellent. The performance of Mn2Sb-based alloys, especially magnetic properties, can be improved by adding magnetic rare earth elements. However, in the process of doping Bi elements, Mn2Sb-based alloys have obvious Bi-rich grain boundary phases, and the grain boundary phase agglomeration phenomenon occurs during the diffusion of Bi elements. This agglomeration phenomenon will seriously affect the magnetic properties of Bi-rich Mn2Sb-based alloys. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for improving the physical properties of Bi-rich Mn2Sb-based alloy materials, and improves the magnetic properties of Bi-rich Mn2Sb-based alloy materials by introducing diffusion sources.
[0005] The present invention provides a method for improving the physical properties of a Bi-rich Mn2Sb-based alloy material, wherein the physical properties are magnetic properties, and the method comprises the following steps:
[0006] The parent alloy and the diffusion source are mixed, and sintered at 500°C to 850°C for 15min to 36min to diffuse the diffusion source into the parent alloy;
[0007] The diffusion source accounts for 2.9% to 30% of the total mass of the parent alloy and the diffusion source;
[0008] The diffusion source is Dy 100-y Cu y , 5≤y≤40 or Pr 100-z Ga z , 5≤z≤40;
[0009] The parent phase alloy is (Mn2Sb) 1-x Bi x , 0<x≤0.2;
[0010] Wherein, x, y, z represent the atomic percentage content.
[0011] The present invention mixes the diffusion source with the parent alloy and controls the diffusion source Dy 100-y Cu y or Pr 100-z Ga z The mass percentage is 2.9% to 30%, and rare earth alloy diffusion is carried out on the grain boundary phase of the material. 1-x Bi x A magnetic grain boundary phase is obtained in the alloy. Sintering at 500℃~850℃ for 15min~36min can make the diffusion source diffuse better in the parent alloy, thereby further improving the magnetic properties of the Bi-rich Mn2Sb-based alloy material. (Mn2Sb) 1-x Bi x , 0<x≤0.2, by changing the value of x to adjust the alloy composition and the amount of Bi-rich grain boundary phase, the grain boundary channel can be controlled, the grain boundary diffusion channel can be adjusted, and the diffusion of rare earth elements can be promoted.
[0012] In another preferred embodiment, the sintering further includes heat treatment;
[0013] The heat treatment refers to annealing at the sintering temperature for 1 to 5 days and then cooling to 21° C. to 25° C. The purpose of uniform diffusion is achieved through heat treatment.
[0014] In another preferred embodiment, the sintering pressure is 15 MPa to 100 MPa.
[0015] In another preferred embodiment, the particle size of the parent phase alloy is 10 μm to 50 μm; the particle size of the diffusion source is 1 μm to 50 μm.
[0016] In another preferred embodiment, the specific preparation process of the parent phase alloy is as follows:
[0017] According to the stoichiometric ratio, the parent alloy raw materials Mn, Sb and Bi are weighed respectively, and the raw materials are mixed and smelted to obtain (Mn2Sb) 1-x Bi x Ingot, (Mn2Sb) 1-x Bi x The ingot is annealed and crushed to obtain the parent phase alloy;
[0018] The specific preparation process of the diffusion source is as follows:
[0019] According to the stoichiometric ratio, the diffusion source raw materials Dy and Cu, or Pr and Ga, are weighed separately, Dy and Cu are mixed, or Pr and Ga are mixed, and smelted to obtain Dy 100-y Cuy Ingot or Pr 100-z Ga z Ingot;
[0020] Dy 100-y Cu y Ingot or Pr 100-z Ga z The ingot is melted into liquid and sprayed onto a rotating copper rod to obtain Dy 100- y Cu y Rapid quenching strip or Pr 100-z Ga z Rapid quenching strip, Dy 100-y Cu y Rapid quenching strip or Pr 100-z Ga z The rapidly quenched strip is crushed to obtain the diffusion source.
[0021] In another preferred embodiment, the melting temperature during the preparation of the parent phase alloy is 950°C to 1000°C, the annealing temperature is 680°C to 700°C, and the annealing time is 5d to 7d;
[0022] The melting temperature in the diffusion source preparation process is 800°C to 900°C.
[0023] In another preferred embodiment, the pulverization is performed by grinding or ball milling.
[0024] In another preferred embodiment, the grinding time is 30 min to 60 min.
[0025] In another preferred embodiment, the forward and reverse rotation speeds of the ball mill are 200 rpm to 500 rpm, the time is 40 min to 60 min, and the cycle is 5 to 10 times.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention comprises the following steps: 1-x Bi x In the parent alloy, rare earth element diffusion source Dy is introduced 100-y Cu y or Pr 100-z Ga z , controlling the sintering temperature can make the rare earth element diffusion source diffuse better to (Mn2Sb) 1-x Bi xIn the parent phase alloy, the phase transition thermal hysteresis after diffusion is greatly reduced, thereby effectively improving the magnetic properties of the Bi-rich Mn2Sb-based alloy material. The Bi-rich Mn2Sb-based alloy material obtained by grain boundary diffusion of rare earth elements has a magnetic grain boundary phase, thereby effectively improving the magnetic properties, making the Bi-rich Mn2Sb-based alloy material have a wider application prospect. And the (Mn2Sb) in the present invention 1- x Bi x ,0<x≤0.2 alloy, by changing the x value to adjust the alloy composition and the amount of Bi-rich grain boundary phase, the grain boundary channel can be controlled, the grain boundary diffusion channel can be adjusted, and the diffusion of rare earth elements can be promoted.
[0028] (2) The method of the present invention can make the Bi-rich Mn2Sb-based alloy material have multifunctional properties, including giant magnetocaloric effect, giant magnetoresistance effect, exchange bias effect and Hall effect, and can be widely used in some basic research fields of phase change physics and potential application fields such as smart materials, information storage, magnetic refrigeration / heat, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The alloy diffusion (Mn2Sb) in Example 1 of the present invention 0.89 Bi 0.11 Horizontal isofield thermomagnetic curve of the alloy sample, where ZFC represents the zero-field cooling curve and FC represents the field cooling curve.
[0030] Figure 2 Dy in Example 1 of the present invention 70 Cu 30 Alloy Diffusion (Mn2Sb) 0.89 Bi 0.11 Vertical equifield thermomagnetic curves of the alloy sample.
[0031] Figure 3 Dy in Example 1 of the present invention 70 Cu 30 Alloy Diffusion (Mn2Sb) 0.89 Bi 0.11 EDS point scanning diagram of the alloy sample, where 1.txt, 2.txt, 3.txt, 4.txt, and 5.txt are the scanning positions.
[0032] Figure 4 Dy in Example 1 of the present invention 70 Cu 30 Alloy Diffusion (Mn2Sb) 0.89 Bi 0.11 Equifield thermomagnetic curves of the alloy sample before and after diffusion.
[0033] Figure 5Dy in Example 2 of the present invention 70 Cu 30 Alloy Diffusion (Mn2Sb) 0.89 Bi 0.11 EDS point scan of alloy sample.
[0034] Figure 6 In Example 3 of the present invention, Pr 80 Ga 20 Alloy Diffusion (Mn2Sb) 0.89 Bi 0.11 EDS point scan of alloy sample. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific examples, but it should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.
[0036] The present invention uses an in-situ grain boundary diffusion method to (Mn2Sb) 1-x Bi x ,0<x≤0.2 alloy, introducing a diffusion source Dy containing rare earth elements 100-y Cu y or Pr 100-z Ga z , through calcination and heat treatment, the diffusion source Dy 100-y Cu y or Pr 100- z Ga z In (Mn2Sb) 1-x Bi x The method of the present invention can be used to obtain a Mn2Sb-based alloy material with a Bi-rich phase and good magnetic properties, wherein the parent phase alloy and the diffusion source are specifically composed as follows:
[0037] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Dy 100-y Cu y , y=5, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0038] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Dy 100-y Cu y , y=5, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0039] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0040] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0041] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Dy 100-y Cu y , y=40, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0042] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Dy 100-y Cu y , y=40), the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0043] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Pr 100-z Ga z , z=5, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0044] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Pr 100-z Ga z , z=5, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0045] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Pr 100-z Ga z , z=20, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0046] Parent alloy (Mn2Sb) 1-x Bix , x = 0.09 and the diffusion source Pr 100-z Ga z , z=20, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0047] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Pr 100-z Ga z , z=40, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0048] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.09 and the diffusion source Pr 100-z Ga z , z=40, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0049] In the above alloys, the x of Bi in Mn2Sb is 0.09. This is mainly because the solubility limit of Bi in Mn2Sb is 7% to 9%. Therefore, the Bi value of 0.09 selected in the present invention is the limit value in Mn2Sb.
[0050] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.11 and the diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0051] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.11 and the diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0052] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.11 and the diffusion source Pr 100-z Ga z , z=20, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0053] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.11 and the diffusion source Pr 100-z Ga z , z=20, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0054] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.2 and the diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0055] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.2 and the diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0056] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.2 and the diffusion source Pr 100-z Ga z , z=20, the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source.
[0057] Parent alloy Mn2Sb) 1-x Bi x , x = 0.2 and the diffusion source Pr 100-z Ga z , z=20, the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source.
[0058] The above are the two end limit values of Bi in Bi-rich Mn2Sb-based alloys, 0% to 0.2%.
[0059] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.11 and rare earth alloy diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 10% of the total mass of the parent alloy and the diffusion source.
[0060] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.11 and the diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 20% of the total mass of the parent alloy and the diffusion source.
[0061] Parent alloy (Mn2Sb) 1-x Bi x , x = 0.11 and the diffusion source Dy 100-y Cu y , y=30, the diffusion source accounts for 30% of the total mass of the parent alloy and the diffusion source.
[0062] The above mentioned are the diffusion source added value limits of 2.9% to 30%.
[0063] Based on the above principle, the present invention provides a Bi-rich Mn2Sb-based alloy material with good magnetic properties. Five methods for improving the physical properties of the Bi-rich Mn2Sb-based alloy material are described below as examples.
[0064] Example 1
[0065] A method for improving the physical properties of a Bi-rich Mn2Sb-based alloy material, wherein the magnetic phase change alloy (Mn2Sb) 0.89 Bi 0.11 is the parent phase, and the diffusion source is Dy 70 Cu 30 , including the following steps:
[0066] S1. Calculate the mass of the required Mn, Sb, Bi, Dy, and Cu elements according to the stoichiometric ratio and prepare the ingredients. The mass of the elements needs to be accurate to three decimal places in milligrams. The purity of Mn and Dy is 99.8%, which is purified by arc melting. The purity of other elements is 99.99%.
[0067] S2, put the elements Mn, Sb, and Bi in S1 into a 950℃ high vacuum melting furnace, and evacuate the furnace chamber to 5×10 - 3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 100A. This process is repeated 4 times to obtain (Mn2Sb) 0.89 Bi 0.11 Ingot;
[0068] The Dy and Cu elements in S1 were placed in a high vacuum melting furnace at 950°C and the furnace chamber was evacuated to 5×10 -3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 100A. This is repeated 4 times to obtain Dy 70 Cu 30 Ingot.
[0069] S3, the obtained (Mn2Sb) 0.89 Bi 0.11 The alloy ingot was annealed at 700℃ for 5 days and then water quenched to obtain (Mn2Sb) 0.89 Bi 0.11 Block.
[0070] S4, Dy 70 Cu 30The ingot was placed in a quartz tube with an inner diameter of 10 mm and an opening diameter of 1 mm. The quartz tube was placed in a high vacuum belt-spinning furnace and the furnace chamber was evacuated to 10 -4 Pa, 0.5 atmospheres of argon gas was introduced, the copper roller speed was adjusted to 24m / s, the induction coil heating current was adjusted, and when the current reached 36A or more, the alloy ingot was observed to turn red. The current was further increased to 41±3A, and the alloy ingot flowed in liquid state. The molten alloy was sprayed onto the rotating copper rod by using the pressure difference jet to quickly solidify and form a fast-quenching strip to obtain Dy 70 Cu 30 Strips.
[0071] S5, (Mn2Sb) 0.89 Bi 0.11 Bulk and Dy 70 Cu 30 The strips were ground with a mortar and then ground with a vibrating ball mill at 50 Hz for 60 min to obtain particles with a size of 500 mesh (Mn2Sb) and 0.89 Bi 0.11 Powder and particle size 300 mesh Dy 70 Cu 30 powder.
[0072] S6、Dy 70 Cu 30 Powder and (Mn2Sb) 0.89 Bi 0.11 The powders are mixed to obtain a mixed powder, in which the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source; the mixed powder is added into a graphite mold, and diffused in a plasma discharge sintering furnace, sintered at a temperature of 800°C for 15 minutes and a pressure of 100 MPa, wherein the heat preservation time is 8 minutes and the pressure preservation time is 2 minutes, and annealed in a muffle furnace at the sintering temperature for 5 days, and then cooled to 21°C with the furnace.
[0073] Example 2
[0074] A method for improving the physical properties of Bi-rich Mn2Sb-based alloy materials, which is a magnetic phase change alloy (Mn2Sb) 0.89 Bi 0.11 is the parent phase, and the diffusion source is Dy 70 Cu 30 , including the following steps:
[0075] S1. Calculate the mass of the required Mn, Sb, Bi, Dy, and Cu elements according to the stoichiometric ratio and prepare the ingredients. The mass of the elements needs to be accurate to three decimal places in milligrams. The purity of Mn and Dy is 99.8%, which is purified by arc melting. The purity of other elements is 99.99%.
[0076] S2, put the elements Mn, Sb, and Bi in S1 into a 1000℃ high vacuum melting furnace, and evacuate the furnace chamber to 5×10 - 3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 100A. This process is repeated 4 times to obtain (Mn2Sb) 0.89 Bi 0.11 Ingot.
[0077] The Dy and Cu elements in S1 were placed in a high vacuum melting furnace at 950°C and the furnace chamber was evacuated to 5×10 -3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 100A. This is repeated 4 times to obtain Dy 70 Cu 30 Ingot.
[0078] S3, the obtained (Mn2Sb) 0.89 Bi 0.11 The alloy ingot was annealed at 680℃ for 7 days and then water quenched to obtain (Mn2Sb) 0.89 Bi 0.11 Block.
[0079] S4, Dy 70 Cu 30 The ingot was placed in a quartz tube with an inner diameter of 10 mm and an opening diameter of 1 mm. The quartz tube was placed in a high vacuum belt-spinning furnace and the furnace chamber was evacuated to 10 -4 Pa, 0.5 atmospheres of argon gas was introduced, the copper roller speed was adjusted to 24m / s, the induction coil heating current was adjusted, and when the current reached 36A or more, the alloy ingot was observed to turn red. The current was further increased to 41±3A, and the alloy ingot flowed in liquid state. The molten alloy was sprayed onto the rotating copper rod by using the pressure difference jet to quickly solidify and form a fast-quenching strip to obtain Dy 70 Cu 30 Strips.
[0080] S5, (Mn2Sb) 0.89 Bi 0.11 Bulk and Dy 70 Cu 30 The strips were ground with a mortar and then ground with a vibrating ball mill at 50 Hz for 60 min to obtain particles with a size of 500 mesh (Mn2Sb) and 0.89 Bi 0.11 Powder and particle size 300 mesh Dy 70 Cu 30 powder.
[0081] S6、Dy 70 Cu 30Powder and (Mn2Sb) 0.89 Bi 0.11 The powders are mixed to obtain a mixed powder, in which the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source; the mixed powder is added into a graphite mold, and diffused in a plasma discharge sintering furnace, sintered at a temperature of 600° C. for 36 min, a pressure of 50 MPa, a heat preservation time of 8 min, and a pressure holding time of 2 min to obtain a Bi-rich Mn2Sb-based alloy material, and annealed in a muffle furnace for 4 days while maintaining the sintering temperature, and then cooled to 21° C. with the furnace.
[0082] Example 3
[0083] A method for improving the physical properties of Bi-rich Mn2Sb-based alloy materials, magnetic phase change alloy (Mn2Sb) 0.89 Bi 0.11 is the parent phase, and the diffusion source is Pr 80 Ga 20 , including the following steps:
[0084] S1. Calculate the required mass of Mn, Sb, Bi, Dy and Cu elements according to the stoichiometric ratio and prepare the ingredients. The mass of the elements needs to be accurate to three decimal places in milligrams. The purity of Mn and Dy is 99.8%, which is purified by arc melting. The purity of other elements is 99.99%.
[0085] S2, put the elements Mn, Sb, and Bi in S1 into a 950℃ high vacuum melting furnace, and evacuate the furnace chamber to 5×10 - 3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 100A. This process is repeated 4 times to obtain (Mn2Sb) 0.89 Bi 0.11 Ingot;
[0086] The Dy and Cu elements in S1 were placed in a high vacuum melting furnace at 950°C and the furnace chamber was evacuated to 5×10 -3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 100A. This is repeated 4 times to obtain Dy 70 Cu 30 Ingot.
[0087] S3, the obtained (Mn2Sb) 0.89 Bi 0.11 The alloy ingot was annealed at 700℃ for 5 days and then water quenched to obtain (Mn2Sb) 0.89 Bi 0.11 Block.
[0088] S4, Dy 70 Cu 30 The ingot was placed in a quartz tube with an inner diameter of 10 mm and an opening diameter of 1 mm. The quartz tube was placed in a high vacuum belt-spinning furnace and the furnace chamber was evacuated to 10 -4 Pa, 0.5 atmospheres of argon gas was introduced, the copper roller speed was adjusted to 24m / s, the induction coil heating current was adjusted, and when the current reached 36A or more, the alloy ingot was observed to turn red. The current was further increased to 41±3A, and the alloy ingot flowed in liquid state. The molten alloy was sprayed onto the rotating copper rod by using the pressure difference jet to quickly solidify and form a fast-quenching strip to obtain Dy 70 Cu 30 Strip.
[0089] S5, (Mn2Sb) 0.89 Bi 0.11 Bulk and Dy 70 Cu 30 The strips were ground with a mortar and then ground with a vibrating ball mill at 50 Hz for 60 min to obtain particles with a size of 500 mesh (Mn2Sb) and 0.89 Bi 0.11 Powder and particle size 300 mesh Dy 70 Cu 30 powder.
[0090] S6、Dy 70 Cu 30 Powder and (Mn2Sb) 0.89 Bi 0.11 The powders are mixed to obtain a mixed powder, in which the diffusion source accounts for 2.9% of the total mass of the parent alloy and the diffusion source; the mixed powder is added into a graphite mold, and diffused in a plasma discharge sintering furnace, sintered at a temperature of 600° C. for 20 min, a pressure of 50 MPa, a heat preservation time of 8 min, and a pressure holding time of 2 min to obtain a Bi-rich Mn2Sb-based alloy material, and annealed in a muffle furnace for 5 days while maintaining the sintering temperature, and then cooled with the furnace.
[0091] Example 4
[0092] A method for improving the physical properties of Bi-rich Mn2Sb-based alloy materials, magnetic phase change alloy (Mn2Sb) 0.89 Bi 0.11 is the parent phase, and the diffusion source is Dy 70 Cu 30 , including the following steps:
[0093] S1. Calculate the required mass of Mn, Sb, Bi, Dy and Cu elements according to the stoichiometric ratio and prepare the ingredients. The mass of the elements needs to be accurate to three decimal places in milligrams. The purity of Mn and Dy is 99.8%, which is purified by arc melting. The purity of other elements is 99.99%.
[0094] S2, put the elements Mn, Sb, and Bi in S1 into a 950℃ high vacuum melting furnace, and evacuate the furnace chamber to 5×10 - 3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 150A. This process is repeated 4 times to obtain (Mn2Sb) 0.89 Bi 0.11 Ingot.
[0095] The Dy and Cu elements in S1 were placed in a high vacuum melting furnace at 950°C and the furnace chamber was evacuated to 5×10 -3 Pa, 0.5 atmospheres of argon gas was introduced, an arc was released through the tungsten electrode, and the above metal raw materials were melted into liquid with a current of 150A. This process was repeated 4 times to obtain Dy 70 Cu 30 Ingot.
[0096] S3, the obtained (Mn2Sb) 0.89 Bi 0.11 The alloy ingot was annealed at 700℃ for 5 days and then water quenched to obtain (Mn2Sb) 0.89 Bi 0.11 Block.
[0097] S4, Dy 70 Cu 30 The ingot was placed in a quartz tube with an inner diameter of 10 mm and an opening diameter of 1 mm. The quartz tube was placed in a high vacuum belt-spinning furnace and the furnace chamber was evacuated to 10 -4 Pa, 0.5 atmospheres of argon gas was introduced, the copper roller speed was adjusted to 24m / s, the induction coil heating current was adjusted, and when the current reached 36A or more, the alloy ingot was observed to turn red. The current was further increased to 41±3A, and the alloy ingot flowed in liquid state. The molten alloy was sprayed onto the rotating copper rod by using the pressure difference jet to quickly solidify and form a fast-quenching strip to obtain Dy 70 Cu 30 Strips.
[0098] S5, (Mn2Sb) 0.89 Bi 0.11 Bulk and Dy 70 Cu 30The strips were ground with a mortar and then ground with a vibrating ball mill at 50 Hz for 60 min to obtain particles with a size of 500 mesh (Mn2Sb) and 0.89 Bi 0.11 Powder and particle size 300 mesh Dy 70 Cu 30 powder.
[0099] S6、Dy 70 Cu 30 Powder and (Mn2Sb) 0.89 Bi 0.11 The powders are mixed to obtain a mixed powder, in which the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source; the mixed powder is added into a graphite mold, and diffused in a plasma discharge sintering furnace, sintered at a temperature of 800° C. for 25 min, a pressure of 50 MPa, a heat preservation time of 8 min, a pressure preservation time of 2 min, annealed in a muffle furnace at the sintering temperature for 4 days, and then cooled to 21° C. with the furnace.
[0100] Example 5
[0101] A method for improving the physical properties of Bi-rich Mn2Sb-based alloy materials, magnetic phase change alloy (Mn2Sb) 0.89 Bi 0.11 is the parent phase, and the diffusion source is Dy 70 Cu 30 , including the following steps:
[0102] S1. Calculate the mass of the required Mn, Sb, Bi, Dy, and Cu elements according to the stoichiometric ratio and prepare the ingredients. The mass of the elements needs to be accurate to three decimal places in milligrams. The purity of Mn and Dy is 99.8%, which is purified by arc melting. The purity of other elements is 99.99%.
[0103] S2, put the elements Mn, Sb, and Bi in S1 into a 950℃ high vacuum melting furnace, and evacuate the furnace chamber to 5×10 - 3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 100A. This process is repeated 4 times to obtain (Mn2Sb) 0.89 Bi 0.11 Ingot;
[0104] The Dy and Cu elements in S1 were placed in a high vacuum melting furnace at 950°C and the furnace chamber was evacuated to 5×10 -3 Pa, 0.5 atmospheres of argon gas is introduced, an arc is released through the tungsten electrode, and the above metal raw materials are melted into liquid with a current of 100A. This is repeated 4 times to obtain Dy 70 Cu30 Ingot.
[0105] S3, the obtained (Mn2Sb) 0.89 Bi 0.11 The alloy ingot was annealed at 700℃ for 6 days and then water quenched to obtain (Mn2Sb) 0.89 Bi 0.11 Block.
[0106] S4, Dy 70 Cu 30 The ingot was placed in a quartz tube with an inner diameter of 10 mm and an opening diameter of 1 mm. The quartz tube was placed in a high vacuum belt-spinning furnace and the furnace chamber was evacuated to 10 -4 Pa, 0.5 atmospheres of argon gas was introduced, the copper roller speed was adjusted to 24m / s, the induction coil heating current was adjusted, and when the current reached 36A or more, the alloy ingot was observed to turn red. The current was further increased to 41±3A, and the alloy ingot flowed in liquid state. The molten alloy was sprayed onto the rotating copper rod by using the pressure difference jet to quickly solidify and form a fast-quenching strip to obtain Dy 70 Cu 30 Strip.
[0107] S5, (Mn2Sb) 0.89 Bi 0.11 Bulk and Dy 70 Cu 30 The strips were ground with a mortar and then passed through a high-energy ball mill. The ball milling conditions were 200 rpm for 60 min and repeated 5 times to obtain particles with a size of 500 mesh (Mn2Sb) 0.89 Bi 0.11 Powder and particle size 600 mesh Dy 70 Cu 30 powder.
[0108] S6、Dy 70 Cu 30 Powder and (Mn2Sb) 0.89 Bi 0.11 The powders are mixed to obtain a mixed powder, in which the diffusion source accounts for 4.8% of the total mass of the parent alloy and the diffusion source; the mixed powder is added into a graphite mold, and diffused in a plasma discharge sintering furnace, sintered at a temperature of 770° C. for 15 min, a pressure of 50 MPa, a heat preservation time of 8 min, and a pressure holding time of 2 min to obtain a Bi-rich Mn2Sb-based alloy material, and annealed in a muffle furnace at the sintering temperature for 4 days, and then cooled to 21° C. with the furnace.
[0109] (Mn2Sb) obtained in Example 1 0.89 Bi 0.11 The diffusion source is Dy 70 Cu 30The determination was performed, wherein Dy 70 Cu 30 The total mass of the parent alloy and the diffusion source is 4.8%. Figure 1 to Figure 4 shown.
[0110] pass Figure 1 and Figure 2 It can be seen that (Mn2Sb) 0.89 Bi 0.11 The diffusion source is Dy 70 Cu 30 When the parent phase and the diffusion source are mixed evenly in both horizontal and vertical cross sections, the thermomagnetic curves under 0.01T and 5T magnetic fields have no obvious deviation, and there is a phase change at low temperature. This is the magnetic change caused by the grain boundary diffusion of the rare earth alloy. According to Table 1 and Figure 3 It can be seen that in the eds point scan, the composition of the second point can indicate that the rare earth element Dy diffuses along the grain boundary and Figure 4 It can be seen that the phase transition thermal hysteresis is greatly reduced after diffusion, indicating that the grain boundary diffusion of rare earth elements is beneficial to improving the magnetic properties of the alloy.
[0111] Table 1 Example 1 (Mn2Sb) 0.89 Bi 0.11 Medium diffusion source Dy 70 Cu 30 The eds point sweep position component
[0112] Scan Point Mn(at%) Cu(at%) Sb(at%) Dy(at%) Bi(at%) 1 40.87 0.04 29.90 20.91 8.27 2 14.55 0.00 8.48 41.81 35.17 3 61.85 1.03 34.86 0.05 2.21 4 66.20 0.91 30.16 0.24 2.49 5 5.98 0.00 36.97 45.72 11.32 6 60.47 0.47 29.75 5.23 4.09
[0113] (Mn2Sb) obtained in Example 2 0.89 Bi 0.11 The diffusion source is Dy 70 Cu 30 The determination was performed, wherein Dy 70 Cu 30 The total mass of the parent alloy and the diffusion source is 2.9%. Figure 5 shown.
[0114] pass Figure 5 From positions 1 and 2 in Table 2, we can see that Dy 70 Cu 30 There is partial diffusion between the alloy and the Bi-rich phase, indicating that the method of diffusing the rare earth alloy along the original Bi-rich grain boundary is feasible. As can be seen from positions 3 and 4, during the diffusion process, large particles of Dy 70 Cu 30 The internal diffusion fails to occur and then combines Figure 3The distribution and agglomeration of Cu atoms in Table 1 indicate that some rare earth elements diffused at 600°C, proving that significant diffusion can also occur at temperatures lower than the melting point of rare earth alloys, i.e., 790°C.
[0115] Table 2 Example 2 (Mn2Sb) 0.89 Bi 0.11 Medium diffusion source Dy 70 Cu 30 The eds point sweep position component
[0116] Scan Point Mn(at%) Cu(at%) Sb(at%) Dy(at%) Bi(at%) 1 4.69 0.00 21.92 56.93 16.47 2 6.67 0.00 14.18 62.26 16.88 3 0.73 29.87 0.15 68.97 0.29 4 0.38 25.62 0.08 73.93 0.00 5 64.10 0.35 34.63 0.00 0.92 6 65.27 0.43 33.33 0.00 0.97
[0117] (Mn2Sb) obtained in Example 3 0.89 Bi 0.11 Medium diffusion Pr 80 Ga 20 The determination was carried out, where Pr 80 Ga 20 The total mass of the parent alloy and the diffusion source is 2.9%. Figure 6 And as shown in Table 3.
[0118] Table 3 Example 3 (Mn2Sb) 0.89 Bi 0.11 Medium diffusion Pr 80 Ga 20 The eds point sweep position component
[0119] Scan Point Mn(at%) Ga(at%) Sb(at%) Pr(at%) Bi(at%) 1 64.63 0.01 34.17 0.01 1.17 2 51.25 0.47 43.63 0.09 4.56 3 49.54 1.02 14.40 3.29 31.75 4 21.12 0.00 0.08 0.36 56.51 5 8.88 0.00 34.63 0.45 54.7 6 8.84 0.00 33.33 0.40 51.07
[0120] Depend on Figure 6 From Table 3, we can see that at a temperature higher than Pr 80 Ga 20 The melting point of the alloy is 580°C, and no obvious grain boundary phase is formed. In addition, the Pr element accounts for a very small proportion in the six positions, which indicates that the process of forming double liquid phase diffusion is still immature above the melting point. Compared with Example 1, different rare earth elements have different effects on the composition of the alloy grain boundary phase.
[0121] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the physical properties of Bi-rich Mn2Sb-based alloy materials, characterized in that: The physical property is magnetic property, and the method comprises the following steps: The parent alloy and the diffusion source are mixed, and sintered at 500°C to 850°C for 15min to 36min to diffuse the diffusion source into the parent alloy; The diffusion source accounts for 2.9% to 30% of the total mass of the parent alloy and the diffusion source; The diffusion source is Dy 100-y Cu y , 5≤y≤40 or Pr 100-z Ga z , 5≤z≤40; The parent phase alloy is (Mn2Sb) 1-x Bi x , 0<x≤0.
2.
2. The method for improving the physical properties of Bi-rich Mn2Sb-based alloy material according to claim 1, characterized in that: The sintering further includes heat treatment; The heat treatment refers to annealing at a sintering temperature for 1 to 5 days and then cooling to 21° C. to 25° C.
3. The method for improving the physical properties of Bi-rich Mn2Sb-based alloy material according to claim 1, characterized in that: The sintering pressure is 15Mpa-100Mpa.
4. The method for improving the physical properties of Bi-rich Mn2Sb-based alloy material according to claim 1, characterized in that: The particle size of the parent phase alloy is 10 μm to 50 μm; the particle size of the diffusion source is 1 μm to 50 μm.
5. The method for improving the physical properties of Bi-rich Mn2Sb-based alloy material according to claim 1, characterized in that: The specific preparation process of the parent phase alloy is as follows: According to the stoichiometric ratio, the parent alloy raw materials Mn, Sb and Bi are weighed respectively, and the raw materials are mixed and smelted to obtain (Mn2Sb) 1-x Bi x Ingot, (Mn2Sb) 1-x Bi x Annealing the ingot and crushing it to obtain the parent phase alloy; The specific preparation process of the diffusion source is as follows: According to the stoichiometric ratio, the diffusion source raw materials Dy and Cu, or Pr and Ga, are weighed separately, Dy and Cu are mixed, or Pr and Ga are mixed, and smelted to obtain Dy 100-y Cu y Ingot or Pr 100-z Ga z Ingot; Dy 100-y Cu y Ingot or Pr 100-z Ga z The ingot is melted into liquid and sprayed onto a rotating copper rod to obtain Dy 100-y Cu y Rapid quenching strip or Pr 100-z Ga z Rapid quenching strip, Dy 100-y Cu y Rapid quenching strip or Pr 100-z Ga z The rapidly quenched ribbon is crushed to obtain the diffusion source.
6. The method for improving the physical properties of Bi-rich Mn2Sb-based alloy material according to claim 5, characterized in that: The melting temperature during the preparation of the parent phase alloy is 950°C to 1000°C, the annealing temperature is 680°C to 700°C, and the annealing time is 5d to 7d; The melting temperature in the diffusion source preparation process is 800°C to 900°C.
7. The method for improving the physical properties of Bi-rich Mn2Sb-based alloy material according to claim 5, characterized in that: The pulverization is performed by grinding or ball milling.
8. The method for improving the physical properties of Bi-rich Mn2Sb-based alloy material according to claim 7, characterized in that: The grinding time is 30 min to 60 min.
9. The method for improving the physical properties of Bi-rich Mn2Sb-based alloy material according to claim 7, characterized in that: The forward and reverse rotation speeds of the ball mill are 200 rpm to 500 rpm, the time is 40 min to 60 min, and the cycle is 5 to 10 times.
Citation Information
Patent Citations
Preparation method for obtaining accurate-composition Mn-Sb-based alloy
CN104073664A
Bi substituted Mn absent Mn2Sb-based alloy and preparation method and application thereof
CN111575532A
Sintered sputtering target material and manufacturing method therefor
JP2009074127A